2017
DOI: 10.1111/btp.12519
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity of a Neotropical amphibian (Engystomops pustulosus) and its vulnerability to climate change

Abstract: A species’ thermal sensitivity and its exposure to climate variation are key components in the prediction of its vulnerability to climate change. We tested the thermal sensitivity of a tropical amphibian that lives in a mild constant climate in which the thermal tolerance range is expected to closely match the experienced environmental temperature. The air temperature that this species is exposed to varies between 21.9 and 31.6°C with an annual mean of 27.2°C. We estimated the microhabitat water temperature va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Considering the current worldwide decline of amphibians ( Alroy, 2015 ; Stuart et al , 2004 ) it is of major interest to investigate whether and how anuran larvae adjust their physiological traits to new thermal challenges and to altered TH status, as caused by natural or anthropogenic stressors in their larval habitat ( Strong et al , 2017 ). Increased metabolic rates are the expected future responses of ectotherms ( Seebacher et al , 2015 ; Berg et al , 2017 ), especially in species with reduced physiological plasticity due to extreme but stable environments as common in tropical species ( Janzen, 1967 ; Huey et al , 2012 ; Oyamaguchi et al , 2017 ). Even though X. laevis is often used for laboratory experiments and, thus, cultured under constant thermal conditions, this is a tropical (Sub-Saharan Africa) species adapted to warm temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the current worldwide decline of amphibians ( Alroy, 2015 ; Stuart et al , 2004 ) it is of major interest to investigate whether and how anuran larvae adjust their physiological traits to new thermal challenges and to altered TH status, as caused by natural or anthropogenic stressors in their larval habitat ( Strong et al , 2017 ). Increased metabolic rates are the expected future responses of ectotherms ( Seebacher et al , 2015 ; Berg et al , 2017 ), especially in species with reduced physiological plasticity due to extreme but stable environments as common in tropical species ( Janzen, 1967 ; Huey et al , 2012 ; Oyamaguchi et al , 2017 ). Even though X. laevis is often used for laboratory experiments and, thus, cultured under constant thermal conditions, this is a tropical (Sub-Saharan Africa) species adapted to warm temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians are ectothermic vertebrates, and high environmental temperatures have direct effects on their behavior and physiology (Rome et al ., 2002; Navas et al ., 2008; Bovo et al ., 2018). Highly heat exposed open forest tropical and subtropical amphibian communities have very low WT, whereas forest species, exposed to cooler environments have larger WT and thus should be less impacted by heat temperatures (Duarte et al ., 2012; Oyamaguchi et al ., 2017; Pintanel et al ., 2019). This suggests that environment may drive thermal variation conditioning organismal risk to suffer acute heat impacts.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we did not account for acclimation or behavioural plasticity, which could reduce extinction risk under climate change ( Ruiz-Aravena et al , 2014 ; Riddell et al , 2018 ). For example, acclimation can increase the CT max of amphibians by up to 4°C ( Brattstrom, 1968 ), but in general, amphibians are thought to have a limited capacity for thermal acclimation ( Niehaus et al , 2012 ; Enriquez-Urzelai et al , 2019 ; Morley et al , 2019 ) and plasticity has been documented more often at colder ( CT min ) than warmer ( CT max ) extremes ( John-Alder et al , 1988 ; Oyamaguchi et al , 2018 ). There has been less research into the potential for amphibians to adapt to increasing water stress, but terrestrial-breeding species can exhibit intraspecific variation in desiccation tolerance ( Rudin-Bitterli et al , 2020 ) and genomic analysis has revealed local adaptation to environmental regimes ( Cummins et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While thermal tolerances can vary according to life stage and acclimation temperature, in amphibians, the CT max of larvae is often higher than that for juveniles and adults but generally varies <1–2°C between life stages ( Krakauer, 1970 ; Delson and Whitford, 1973 ; Cupp, 1980 ; Sherman and Levitis, 2003 ; Beltrán et al , 2019 ; Enriquez-Urzelai et al , 2019 ). Likewise, CT max can vary with acclimation temperature, but on a similar scale of 1–2°C ( Krakauer, 1970 ; Gvoždík et al , 2007 ; Oyamaguchi et al , 2018 ; Enriquez-Urzelai et al , 2019 ). Therefore, we considered our thermal sensitivity estimates based on embryonic and larval development to be informative for assessing thermal stress across all G. alba life stages.…”
Section: Methodsmentioning
confidence: 99%